Size and number variation of adipocytes during the growth of Rasa Aragonesa lambs - Purroy A.; Mendizábal J.A.; Soret B.; Horcada A.; Lizaso G.; Mendizábal F.J.; Arana A. (Body condition of sheep and goats: Methodological aspects and applications, 1995)
The size and number of adipocytes of different fat depots was studied in 45 male lambs of the Rasa Aragonesa breed, distributed in three groups of 15 lambs (G12, G24, G36), slaughtered respectively at 11.7 plus ou moins 0.67, 24.5 plus ou moins 0.57 and 35.8 plus ou moins 1.74 kg live weight (LW) and at an age of 32 plus minus 5, 89 plus minus 8 and 123 plus minus 8 days. G12 lambs were slaughtered on the day of weaning, G24 and G36 lambs were weaned respectively at 16.2 plus minus 1.32 and 18.3 plus minus 2.46 kg LW and were fed from then onwards on concentrated fodder and barley straw ad libitum until they were slaughtered. The results obtained show that there is a significant increase in the amount of fat deposited in three internal (omental, mesenteric and kidney knob and channel) fat depots as the LW at slaughter increases (P less than 0.01). A similar phenomenon occurs in the size of the adipocytes, hypertrophy being more evident between 24 and 36 kg (P less than 0.01) than between 12 and 24 kg, except in the intermuscular fat depot, where the differences were between the two most extreme weights (P less than 0.01). The number of adipocytes in the omental and mesenteric fat depots increased significantly during the period of the study (P less than 0.01), while no variation occurred in the kidney knob and channel fat depot during the same period.
Seminar of the Working Group on Body Condition of Sheep and Goats of the FAO/CIHEAM Network on Sheep and Goats, 24-31 Mar 1994, Zaragoza (Spain)